Physical insight into the accuracy of finely-resolved iLES in turbulent boundary layers. (30th June 2018) - Ritos, Konstantinos; Kokkinakis, Ioannis W.; Drikakis, Dimitris
Highlights: Physical insight into the accuracy of iLES methods for turbulent boundary layers. Order of accuracy in iLES affects turbulence anisotropy and symmetry. Highest anisotropy correlates with maximum Reynolds stress and minimum flatness. High-order iLES comparable to DNS using coarser resolution. Abstract: This paper investigates the numerical accuracy of implicit Large Eddy Simulations (iLES) in relation to compressible turbulent boundary layers (TBL). iLES are conducted in conjunction with Monotonic Upstream-Centred Scheme for Conservation Laws (MUSCL) and Weighted Essentially Non-Oscillatory (WENO), ranging from 2nd to 9th-order. The accuracy effects are presented from a physical perspective showing skewness, flatness and anisotropy calculations, among others. The order of the scheme directly affects the physical representation of the TBL, especially the degree of asymmetry and anisotropy in the sub-layers of the TBL. The study concludes that high-order iLES can provide an accurate and detailed description of TBL directly comparable to available DNS and experimental results.